Measurement of Yangtze River Flow Based on Coastal Acoustic Tomography. Issue 1 (January 2021) - Chen, Zhengwei; Zheng, Hong; Tang, Yunfeng; Chen, Chao
Abstract: River flow is an important hydrological element for river management, and it can be used to detect the profile of river water resources. Coastal acoustic tomography technology, is a novel flow measurement technology, can continuously observe flow changes compared to the acoustic Doppler velocity profiler (ADCP) flow measurement. In this article, our experiment has arranged two acoustic tomography stations on both banks near the Datong Hydrological Station in the Yangtze River. Each station is equipped with a coastal acoustic tomography system. The depth of the transducer placed underwater is about 7 meters, the frequency of the transmitted signal is 50kHz. Knowing the distance between the two stations, calculate the average flow velocity between the stations according to the reciprocal propagation time difference between the stations, and then obtain the average velocity of the section according to the geometric relationship between the flow velocity between the stations and the section velocity. Finally the cross-sectional velocity multiplied by the cross-sectional area is the cross-sectional flow, and the calculation result of the river flow is compared with the official data. Experimental results prove that coastal acoustic tomography technology has broad prospects in monitoring river flow.